The complete guide to core stability - Lawrence, M. (A & C Black Publishers Ltd., 2011)
The Complete Guide series is designed for the fitness professional, coach and student, packed with ready-made training programmes, tips and strategies. This is a new edition of the definitive 'core stability' training handbook for fitness leaders and enthusiasts in an 'all you need to know format. Core stability concentrates on core abdominal muscle strength to improve posture, strength and performance. This book looks at what core stability is, the muscles that are involved, and the benefits to improving your core stability. Including new exercises,with specific exercises for different sports, this new edition covers the use of a variety of equipment - from medicine balls to core boards to the new big thing in core stability - TRX training.